Harmonic wavelets in boundary value problems for harmonic and biharmonic functions - Subbotin, Yu. N.; Chernykh, N. I. (Proceedings of the Steklov Institute of Mathematics, 2011)
We consider boundary value problems in a disk and in a ring for homogeneous equations with the Laplace operator of the first and second orders. Solutions are represented in terms of bases of harmonic wavelets in Hardy spaces of harmonic functions in a disk and in a ring, which were constructed earlier.